Carcass characteristics and meat quality of Hereford sired steers born to beef-cross-dairy and Angus breeding cows. - Coleman LW; Hickson RE; Schreurs NM; Martin NP; Kenyon PR; Lopez-Villalobos N; Morris ST (My University, 2016)
Steers from Angus, Angus×Holstein Friesian, Angus×Holstein Friesian-Jersey and Angus×Jersey cows and a Hereford sire were measured for their carcass and meat quality characteristics. Steers from the Angus×Holstein Friesian cows had a greater final body weight and carcass weight (P<0.05). Steers from Angus×Jersey cows had the lowest carcass weight and dressing-out percentage (P<0.05). There was a greater fat depth over the rump at 12 and 18months of age for the steers from Angus cows (P<0.05) but, not at 24months of age. The steers had similar meat quality characteristics across the breed groups. Steers from Angus×Holstein Friesian and Angus×Jersey cows had a higher ratio of n6 to n3 fatty acids. Using beef-cross-dairy cows to produce steers for meat production does not impact on meat quality. Using Jersey in the breed cross reduced the carcass tissues in the live weight and the potential meat yield.
Keywords: Beef; Meat; Quality; Breed; Dairy; Carcass; 0702 Animal Production; 0904 Chemical Engineering; 0908 Food Sciences